Prognostic analysis of extrameningeal solitary fibrous tumor using the modified Demicco model: a clinicopathologic study of 111 Chinese cases - Yao, Chen-chen; Zhou, Jian; Li, Xiao; Yang, Jun; Chen, Gang; Wei, Jia; Fan, Qin-he; Gong, Qi-xing (Frontiers in Oncology, 2024)
Introduction Solitary fibrous tumor (SFT) represents a fibroblastic neoplasm exhibiting NAB2::STAT6 gene rearrangement, displaying diverse clinical manifestations, spanning from benign to malignant. To predict prognosis, the modified (four-variable) Demicco (mDemicco) model was introduced. This investigation aims to authenticate the mDemicco risk model’s precision in Asian patients while investigating the clinicopathological and molecular factors linked to the prognosis of extrameningeal SFTs. Methods Clinicopathological data from 111 extrameningeal SFT cases in East China, covering the period from 2010 to 2020, were thoroughly analyzed. The tumors were classified using the mDemicco model. Immunohistochemical evaluation of P16 and P53, molecular detection of TP53 and TERT promoter mutation, and fluorescence in situ hybridization for CDKN2A gene alterations were performed. Statistical methods were utilized to assess the associations between clinicopathological or molecular factors and prognosis. Results Histologically, only one parameter, the mitotic count, exhibited a statistical correlation with progression-free survival (PFS) and overall survival (OS). During the Kaplan-Meier analysis, the variation in PFS among the different risk groups exhibited a notable trend towards statistical significance. Nevertheless, 3 out of 74 patients classified as low-risk SFTs and 7 out of 21 patients classified as intermediate-risk exhibited disease progression. Among the 5 patients with TP53 mutations and/or mutant-type P53 immunophenotype, 3 experienced disease progression, including 2 intermediate-risk patients. Additionally, among the 4 patients with TERT promoter mutations who were followed up, 3 showed progression, including 2 intermediate-risk patients. Moreover, it was observed that hemizygous loss of CDKN2A was detected in more than 30% of one case, yet the patient exhibited a favorable survival outcome. Conclusion The mDemicco risk model exhibits certain limitations when dealing with smaller tumor sizes, younger age groups, and occurrences of malignant and dedifferentiated SFTs. Furthermore, molecular factors, such as TP53 or TERT promoter mutations, may identify intermediate-risk SFTs with poorer prognoses.